MANAJEMEN MAJELIS ULAMA INDONESIA DALAM PELAKSANAAN MANASIK HAJI KABUPATEN MANDAILING NATAL - Rizky Mubarok Panggabean; Irwan Efendi, Imam Syafi’I, Ahmad Jasa, Kaddar Nasution (JOURNAL OF COMMUNITY DEDICATION, 2023)
This research aims to assess the extent of Management of MUI Mandailing Natal Regency in the implementation of Hajj rituals for prospective pilgrims, kindergarten children and boarding school students. The implementation of this research involves various individuals from various parties involved in this community service effort. This research method uses the Participation Action Research (PAR) method. The results of this service research show that how the management of the Indonesian Ulema Council of Mandailing Natal Regency in the implementation of Hajj rituals is very important because it can help the duties of the Ministry of Religion and help prospective pilgrims in knowing and understanding how the rules and laws during the process of implementing the Hajj pilgrimage will be carried out by pilgrims who will go to fulfil God's call to the holy land. Furthermore, this analysis also shows that there are several methods used by MUI Mandailing Natal Regency in implementing Hajj rituals.